Intermediate sanctions in corrections - Caputo, Gail A., 1965- (North Texas crime and criminal justice series ;, 2004)
This book looks intermediate sanctions systems and their individual programs. It begins with an overview of the background and foundation of intermediate sanctions programs and then describes in clear detail each program and its effectiveness.